Petrogenesis of the Cretaceous Intraplate Mafic Intrusions in the Eastern Tianshan Orogen, NW China - Zhang, Weifeng; Deng, Xin; Tu, Bing; Peng, Lianhong; Jin, Xinbiao (Frontiers in Earth Science, 2021)
In this study, we conducted zircon U-Pb dating, and whole-rock geochemical and Sr-Nd isotope analyses on the Late Mesozoic dolerite dykes in the Eastern Tianshan (NW China) to unravel their petrogenesis and regional tectonic significance. Zircon U-Pb dating on the dolerite yielded an Early Cretaceous age of 129.7 ± 1.4 Ma. The dolerite is calc-alkaline sodic (Na2O/K2O = 4.71 to 6.80), and enriched in LILEs (Rb, K, Sr and Pb) but depleted in HFSEs (Nb, Ta, and Ti). The intermediate Nb/U (16.7 to 18.5) and Ce/Pb (6.33 to 6.90) values, and the presence of xenocrystic zircons in these dolerite dykes suggest crustal assimilation during the magma evolution. Petrological modelling suggests fractionation of olivine, pyroxene, garnet, and spinel in the magma. All the dolerite samples have low initial 87Sr/86Sr (0.7041 to 0.7043) and positive εNd(t) (+4.6 to +5.1) values, indicative of a depleted asthenospheric mantle source. Partial melting modelling suggests that the melting has occurred in the spinel-garnet stability field. Integrating the data from deposit geology, geochronology, geochemistry and Sr-Nd isotopes, we proposed that the Late Cretaceous Eastern Tianshan mafic magmatism was developed in an intraplate extension setting.